Adoption of Improved Scientific Practices of Composite Carp Culture Technology in South 24 Parganas (Indian Journal of Extension Education, 2020)
The study was undertaken in South 24 Paraganas district of West Bengal with an aim to study the adoption of Composite Carp Culture technology. Primary data were collected from 142 fish farmers practicing composite carp culture using structured schedule. The study indicates that 16.2, 61.3 and 22.5 per cent of the respondents were in the category of high, medium and low level of adoption, respectively. Supplementary feeding with pellet feed and careful disposal of dead animals were the most widely adopted practices in carp culture by the farmers. A positive and significant correlation of education level, exposure to mass media, knowledge level, extension contact and experience with level of adoption of composite carp culture technology was observed. A set of 7 independent variables collectively explains 68 percent (R2= 68%) of the variation in adoption of the technology.